The incidence of renal calcification in preterm infants. Issue 4 (April 1991) - Short, A; Cooke, R W
Abstract : A total of 79 infants born at less than 32 weeks' gestation were studied with serial renal ultrasound scans to assess the incidence of nephrocalcinosis. Twenty one infants developed renal calcification giving an overall incidence of 26.6% in the study group. Affected infants were significantly smaller (mean (SD) birth weight 940 (323) g) and significantly less mature (mean (SD) gestation 26.9 (1.9) weeks). In 17 patients the calcification was represented by hyperechogenic renal pyramids alone, and in four patients renal calculi were demonstrated. Factors associated with renal calcification included hypophosphataemia, hypercalcaemia, hypercreatininaemia, and prolonged oxygen requirement during the first month of life. Multivariate analysis showed that the strongest clinical indicator of calcification was duration of oxygen treatment. Infants who still required oxygen treatment at 28 days had a 62% chance of developing renal calcification.